BIOM-03. COMPREHENSIVE GENOMIC AND IMMUNE PROFILING OF NON-SMALL CELL LUNG CANCER BRAIN METASTASES REVEALS LOW TUMOR INFLAMMATION AND ELEVATED CANCER TESTIS ANTIGEN BURDEN. (14th November 2022) - Seager, R J; Pabla, Sarabjot; Achyut, B R; Nesline, Mary; Kannan, Geoffrey; Chenn, Anjen; Zhang, Shengle; Klein, Roger; Conroy, Jeffrey; Sausen, Mark; Saini, Kamal; Jensen, Taylor; et al.
Abstract: BACKGROUND: Non-small cell lung cancer (NSCLC) accounts for 50% of brain metastases. We present the genomic and immune biomarker landscape for a cohort with metastatic NSCLC to the brain. METHODS: We analyzed brain metastases FFPE tissue (n=137; ages 40-85y (mean 65y), 52% female, 48% male) vs. primary sites (n=5533; ages 24-100+y (mean 71y), 51% female, 49% male) for advanced or metastatic NSCLC patients with comprehensive genomic and immune biomarker profiling, including PD-L1 IHC, tumor mutational burden (TMB), Tumor Immunogenic Signature (TIGS), Cell Proliferation (CP), and Cancer Testis Antigen Burden (CTAB). RESULTS: Genomic alteration (GA) frequency for NSCLC brain metastasis versus primary sites were similar among the most frequently mutated genes except for KRAS which was significantly higher among brain metastases (39.9% vs 25.5%, p< 0.0005). No significant differences were observed for TP53 (50.7% vs 50.2%), STK11 (11.5% vs 10.9%), CDKN2A (10.1% vs 7%), or EGFR (8.0% vs 11.5%). PD-L1 expression for all cases by IHC was not significantly different (mean TPS 29.9% vs 26.3%); however, brain metastases were more likely to be PD-L1 negative (TPS< 1%) (46.3% vs 33.3%, p< 0.005). Conversely, TMB was higher in brain metastases versus primary sites (12.9 vs 10.2 muts/MB, p< 8x10 -10 ), with more TMB-high cases (10 muts/Mb) (57.0% vs 33.5%, p< 3x10 -8 ). Similarly, brain metastases had a higher proportion of CTAB-high cases (68.6% vs 57.6%, p=0.01). The immune response biomarker score, TIGS, was more often weak in brain metastases (52.6% vs 34.0%, p< 9x10 -6 ). CONCLUSION: In NSCLC, metastatic brain lesions have a larger antigen burden, with increased TMB and CTAB, likely due to the immune privileged nature of the brain, which is reflected in the lower TIGS scores and PD-L1 positivity. Despite lower PD-L1 positivity, NSCLC brain metastases with negative PD-L1 IHC may potentially benefit from immunotherapy strategies given the high TMB and CTAB.